DIALECTS AS A MEANS OF CREATING INDIVIDUAL SPEECH IN ARTISTIC DISCOURSE (Scientific journal of the Fergana State University, 2025)
Human speech has the following forms, depending on the communicative situation, the content of the information, the purpose of the speaker or writer, as well as the nature of the language form he uses and the style of speech: literary speech, dialectal speech; colloquial speech, literary colloquial speech, slang speech; scientific speech, artistic speech, solemn speech or mourning speech, letter speech or official speech, etc. In these speech forms, the capabilities of the Uzbek language system are used in one way or another. The article discusses dialects, which are a type of sociolects. It discusses the opinions of linguists about dialects, and lists the differences between dialectisms and standart words typical of the literary language. In addition, the stylistic goals and tasks of individualizing the language of characters in artistic discourse, that is, the need to give the environment, without separating them from the territory and environment in which they live are revealed with the help of examples.